(untitled) (American Journal of Islam and Society, 2011)
Being Young and Muslim is a compilation of narratives that address the cultural politics of Muslim youth from multiple perspectives—youthful lifestyles, rebellion, and accommodations signify the “intricate relationship between the young, youth identities and Islam” (19). The volume is divided into five parts. Each part contains several chapters and contextualizes an aspect associated with being young and Muslim. Most of the chapters in this volume were produced for two international workshops on the “Making of the Muslim Youth” that were presented in Leiden in February 2005 and in The Hague in October 2006 (v). In the first chapter “Introduction: Being Young and Muslim in Neoliberal Times,” Linda Herrera and Asef Bayat present the focal points to be addressed throughout the volume: the approaches and directions Muslim youth will undertake in an era with “multiple constraints and opportunities of being young, Muslim, marginalized, and subjects of social control” (11) ...